Effects of Process Oriented Approach to Teaching Writing to English Department Students - Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2012)
This study investigated the effects of process oriented approach to teaching writing to the English Department students. It was a one-shot case study. The subjects were English Department students of Widya Mandala Catholic University Surabaya taking the Writing Course I for 14 meetings focusing on the recount, biography and narrative genres in the academic year 2006-2007. The study revealed that the writing processes taken by the students varied according to the types of writers (the good and the poor). The study also proved that to some extent writing processes the students took had significant effects on the English texts they composed